Kind Automated Medicine Allocator with LED Alarm: K.A.M.A.L.A. - N. Geetha Charmi; A. Pravallika (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
The K.A.M.A.L.A. which is the Kind Automated Medicine Allocator with LED Alarm is a device which is designed to keep the worst nightmare for the aged people or any person who is suffering from early stages of short-term memory or memory loss. Diseases like schizophrenia, Alzheimer’s disease, Vascular dementia, Creutzfeldt-Jakob disease, HIV/AIDS, syphilis, and Lyme disease can cause dementia and most of them are non-curable. Keeping this in mind and empathizing with the close family of the patient suffering from these diseases is the reason behind thinking of this very useful device. The main purpose of this system is to help patients, primarily seniors, take their medications on time in an easy way without the possibility of missing pills, and also reduce the risk of over or overdosing accidentally. This device is designed in such a way that it will remind the consumer to take his/her medication at a customized time using a buzzer. The buzzer will go off once the consumer picks up the tablet from the particular cap which will be indicated with an LED. Also, once the consumer picks up the tablet an “SMS” will be sent to the customized numbers of the medical personnel or the family member who monitors them. Not taking medications correctly can have serious consequences such as delayed recovery, illness and even death.